Optimisation of Malting Parameters for Quinoa and Barley: Application of Response Surface Methodology - Chawanda, Esther Tatenda; Manhokwe, Shepherd; Jombo, Talknice Z; Mugadza, Desmond T; Njini, Michael; Manjeru, Pepukai (Hindawi, 2022)
Quinoa (Chenopodium quinoa Willd) is a nutritious pseudocereal that is more stress-tolerant compared with traditional cereals. It is an excellent example of a climate-smart crop that is more resilient to climate change compared with barley. The purpose of the study was to investigate the optimum malting conditions required to produce quinoa malt using barley as a control. Response surface methodology (RSM) was used to investigate the influence of the two malting parameters steeping time and germination time on Brix (wort extract), diastatic power (DP), and free amino nitrogen (FAN) of the malt. The temperature was set at 15°C during the steeping process. Steeping time ranging from 12 to 48 hours and germination time ranging from 24 to 96 hours were designed using a central composite design (CCD). The kilning temperature for all malts was 65°C. For quinoa malt, there was a notable weak positive correlation between germination time and Brix (r = +0.119). However, there was a strong positive correlation between steeping time and diastatic power (r = +0.893). A similar trend was noted for barley with a weak positive correlation between germination time and Brix (r = +0.142). A strong positive correlation was also recorded between steeping time and diastatic power (r = +0.897) during the malting of barley. There was a relatively stronger correlation between steeping time and FAN (r = +0.895) than germination time and FAN (r = +0.275) in quinoa malt. The optimum values for the malting of barley were 47.68 hrs steeping time and 82.55 hrs germination time with a desirability value of 1.00. The responses for the optimised barley malt were 8.25°Bx, 162.28 mg/L, and 271.69°L for Brix, FAN, and diastatic power, respectively. To produce quinoa malt with Brix, FAN, and diastatic power of 8.37°Bx, 165.60 mg/L, and 275.86°L, respectively, malting conditions of 47.69 hrs steeping time and 95.81 hrs germination time are required. It was noted that quinoa is a very good candidate for producing high-quality malt for the brewing process.